2016
DOI: 10.1038/ncomms11225
|View full text |Cite
|
Sign up to set email alerts
|

Linking stress-driven microstructural evolution in nanocrystalline aluminium with grain boundary doping of oxygen

Abstract: The large fraction of material residing at grain boundaries in nanocrystalline metals and alloys is responsible for their ultrahigh strength, but also undesirable microstructural instability under thermal and mechanical loads. However, the underlying mechanism of stress-driven microstructural evolution is still poorly understood and precludes rational alloy design. Here we combine quantitative in situ electron microscopy with three-dimensional atom-probe tomography to directly link the mechanics and kinetics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…This has enabled the emergence of atom probe crystallographic studies (Vurpillot et al, 2001; Moody et al, 2009; Gault et al, 2012 a ), which facilitate calibration of the reconstruction and advanced reconstruction approaches such as lattice rectification (Vurpillot et al, 2003; Moody et al, 2014; Breen et al, 2015), as well as the opportunity to fully define the crystallographic nature of individual grain boundaries and compare this directly to interfacial chemistry (Araullo-Peters et al, 2012; Yao, et al, 2013). It is possible to conduct chemico-textural orientation mapping at resolutions otherwise not available (Yen et al, 2015; He et al, 2016). However, there remain significant limitations and challenges with this avenue of APT analysis.…”
Section: Introductionmentioning
confidence: 99%
“…This has enabled the emergence of atom probe crystallographic studies (Vurpillot et al, 2001; Moody et al, 2009; Gault et al, 2012 a ), which facilitate calibration of the reconstruction and advanced reconstruction approaches such as lattice rectification (Vurpillot et al, 2003; Moody et al, 2014; Breen et al, 2015), as well as the opportunity to fully define the crystallographic nature of individual grain boundaries and compare this directly to interfacial chemistry (Araullo-Peters et al, 2012; Yao, et al, 2013). It is possible to conduct chemico-textural orientation mapping at resolutions otherwise not available (Yen et al, 2015; He et al, 2016). However, there remain significant limitations and challenges with this avenue of APT analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Upon the journey to ambient or elevated homologous temperatures, thermal energy and/or deformation [64][65][66] can perturb the delicate metastable nanocrystalline state, which often brings decreases in strength via grain growth to a larger, more thermodynamically preferable size. [67][68][69][70][71][72][73][74] In the absence of extrinsic stabilization, the grains grow and strength properties are lost. In Figure 5, Weissmu¨ller [75] presents a schematic that illustrates two alloy states proposed by Gleiter, [7] but includes a new principle where solutes with large enthalpies of segregation have energetically minimized the specific grain boundary energy through segregation to the grain boundary.…”
Section: Low On Energy: Thermodynamic (And Kinetic) Pathways To mentioning
confidence: 99%
“…[126] Subsequently, he and co-workers used in-situ electron microscopy and 3D atom probe to explore the mechanics and kinetics of the oxygen stabilization, and quantify the excess boundary solute clusters needed for stabilization. [127] On the powder metallurgy side of things, cryomilling studies on the effects of O and N in Cu showed that in the as-cryomilled condition, the NC (~45 nm grain size) ''alloy'' had a composition including 0.512 pct O, 0.26 pct N, 0.027 pct C, 0.064 pct Fe, < 0.0005 pct Al, and 0.0094 pct Cr (all in wt pct). [128] The O and N contents in the starting powder were 0.45 and 0.004 wt pct, respectively, indicating the pick-up of both elements during cryomilling.…”
Section: On the Role Of ''Dirt'' On Grain Boundary Stabilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The notion of stabilizing nanocrystalline structures through grain boundary doping has been substantiated for a range of binary alloy systems at temperatures approaching 30% of their melting point [47][48][49]. Stabilization against mechanical grain growth has also been accomplished in nanocrystalline aluminum directly through the addition of grain boundary solute atoms [50] and indirectly through the presence of impurities [51] that effectively pin the boundaries against sliding and/or migration under stress. In the absence of stress-assisted grain growth, a transition to competing deformation mechanisms can be expected that will depend on the nanocrystalline grain size as well as extrinsic factors such as temperature and strain rate.…”
Section: Introductionmentioning
confidence: 99%